Kamchatka, Russia, scale 1:800,000-1:1,200,000 / [prepared for] ITM - Assot︠s︡iirovannyĭ kartograficheskiĭ t︠s︡entr (Moscow, Russia) (International Travel Maps (Firm); ITMB Publishing Ltd., 2005)
Tourist maps of entire Kamchatka Oblast with physical relief emphasized.; Relief shown by gradient tints and spot heights.; Panel title.; At head of titles: International Travel Maps.; Copyright: ITMB Publishing Ltd. 2005.; Includes text, ancillary map of internal administrative divisions, coverage map, publisher's map list, and color illustrations; Insets: Petropavlovsk-Kamchatsky, scale 1:30 000 -- Geysers Valley, scale 1:8 000 -- Commander Islands (Komandorskiye ostrova), scale 1:1 200 000. [Southern Kamchatka Peninsula] -- [Northern Kamchatka Oblast]. Color; 1:800,000 and 1:1,200,000